Awareness, potential factors, and post-amputation care of stump flexion contractures among transtibial amputees - Ghazali, Mohd Fazli; Razak, Nasrul Anuar Abd; Abu Osman, Noor Azuan; Gholizadeh, Hossein (Turkish Society of Physical Medicine and Rehabilitation, 2018)
Objectives: This study aims to assess the level of awareness of transtibial amputee patients on stump contractures and their compliance with efforts implemented to prevent the condition. Patients and methods: This study included 50 unilateral transtibial amputees (26 males, 24 females; mean age 55.4±14.7 years; range, 18 to 78 years) who met the respondent criteria of the study. The respondents were randomly selected and were issued with a questionnaire. Results: The majority of the transtibial amputees were aware of stump contracture complications. It was found that they also preferred methods of prevention which required less effort, was cost-effective, and were also practical. Conclusion: More focus should be placed on contracture prevention methods which were most complied with by the patients. This is because the effectiveness of a prevention method is highly influenced by patients’ compliance with the method. Patients with a higher risk of developing stump contractures should be also given more attention in post-amputation care.